Hydrogen sulfide and sulfaceutic or sulfanutraceutic agents: Classification, differences and relevance in preclinical and clinical studies - A. Martelli; R. d'Emmanuele di Villa Bianca; G. Cirino; R. Sorrentino; V. Calderone; M. Bucci (Elsevier, 2023)
Hydrogen sulfide (H2S) has been extensively studied as a signal molecule in the body for the past 30 years. Researchers have conducted studies using both natural and synthetic sources of H2S, known as H2S donors, which have different characteristics in terms of how they release H2S. These donors can be inorganic salts or have various organic structures. In recent years, certain types of sulfur compounds found naturally in foods have been characterized as H2S donors and explored for their potential health benefits. These compounds are referred to as ''sulfanutraceuticals,'' a term that combines ''nutrition'' and ''pharmaceutical''. It is used to describe products derived from food sources that offer additional health advantages. By introducing the terms ''sulfaceuticals'' and ''sulfanutraceuticals,'' we categorize sulfur-containing substances based on their origin and their use in both preclinical and clinical research, as well as in dietary supplements.